Behaviour of hybrid ferrocement slabs subjected to impact - Shri, S.Deepa; Thenmozhi, R.; Anitha, M. (Journal of Structural Engineering, 2024)
An experimental programme was carried out to study the behaviour of Hybrid Ferrocement (HF) slabs subjected to Impact load. In this study, specimens were ferrocement slab panels - made up of polypropylene fiber reinforced self-compacting concrete (SCC) and are named as Hybrid ferrocement slab. Each of 300 X 300 mm size with varying parameters such as depth of slab (25 & 30 mm), number of layers of weld mesh (2 and 3 layers bundled), number of layers of Glass Fibre Reinforced Polymer (GFRP) wrapping (1 and 2 layers) with two different mixes were cast. Totally 72 slabs with auxiliary specimens were cast and tested. Impact load was applied by means of hammer of weight 3.5 kg (34.335 N). The test results revealed that the addition of fibers increases the energy absorption characteristics of Hybrid Ferrocement (HF) slabs when compared to the slabs without fibers. The influence of polypropylene fibers, thickness of HF slabs, number of weldmesh layers, laminating with one and two number of GFRP layers were investigated in a detailed manner. In the HF slabs of 30mm thickness, 3 layers bundled with 2 layers of GFRP wrapping absorb more impact energy and resulted in more ductility index when compared to their counterparts. It was concluded that the energy absorption was increased due to the increase in volume fraction of reinforcement and the better confinement provided by GFRP wrapping in tension zone.